Baseline Compliance Assessment Survey for Cigarettes and Other Tobacco Products Act 2003 in Eight Districts of Maharashtra - Jagdishchandra Vathar; Harshal P Bafna; Maya S Indurkar; Appasahe Ugale (Journal of Indian Association of Public Health Dentistry)
Background: The prevalence of overall tobacco use in Maharashtra has reduced by 4.8% from the Global Adult Tobacco Survey (GATS-1) to GATS-2, but it suggested a significant need in terms of awareness and enforcement of tobacco control laws along with strengthening of the institutional mechanism of District Tobacco Control Cell, sensitization, and capacity building of the stakeholders. Compliance assessments are one of the most uncomplicated and cost-effective instruments for measuring and shaping the progress of implementation. Hence, Government Dental College and Hospital Aurangabad along with the Director of health services, Maharashtra, Marathwada Gramin Vikas Sanstha, and The Union has conducted compliance Assessments of Sections 4, 5, 6-a, and 6-b, and 7, 8, and 9 of Cigarettes and Other Tobacco Products Act (COTPA) Act in 8 districts, namely Nandurbar, Satara, Solapur, Pune, Kolhapur, Jalgaon, Sangli, and Dhule project districts of Maharashtra state. Methodology: A cross–sectional descriptive study was conducted in 8 districts of Maharashtra region and a Checklist pertaining to Section 4, 5, 6, 7, 8, and 9 were recorded. Results: Pune showed the highest Smoking signages with 75% coverage, but active smoking was also seen at 70% of public places with tobacco products being advertised at 55.71% of PoS. 75.56% of schools displayed the signage in their premises in Nandurbar, but the sale of tobacco products within 100 yards was seen highest in 78.57% of Pune schools, whereas in Satara, minors were found selling tobacco at 40% of locations. Conclusion: Implementation of COTPA remains ineffective and only to a certain amount, whereas stricter measures are needed to be taken by the authorities.